Invitation to Didactique - Warfield, Virginia McShane; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Didactique is a research program in mathematics education that was launched in France in the 60's and now engages many researchers, from graduate students to senior professors. Until the 90's, almost none of its ideas and results were available to Anglophones. Since that time, a book and some articles have been published in English, but they tend to be accessible only to those who already have some expertise in mathematics education. This book is designed for the interested non-expert, or, alternatively, the expert who would like to hit the high spots of Didactique swiftly. It is designed to pique the interest of both sufficiently to entice them into digging further.
1. Basic elements of Didactique -- 2. Two illustrative examples -- 3. A fundamental situation for statistics -- 4. Gael and the didactical contract -- 5. Glossary -- Index -- Bibliography.
Keywords: Education; Mathematics; Education; Education (general).; Mathematics Education